Assessment of interleukin-28B (interferon λ3) rs12979860 C/T gene polymorphism and the risk for hepatocellular carcinoma in chronic hepatitis C cirrhotic patients. Issue 3 (July 2016) - Teama, Salwa H.H.; Agwa, Sara H.A.; El Sayed, Osama A.E.; Sayed, Moataz M.; Abd El Samee, Aya; El Nakeep, Sarah
Abstract : Introduction: Hepatitis C virus (HCV) infection endemicity in Egypt is an important risk factor for the high prevalence of hepatocellular carcinoma (HCC). This mandates an exploration of the underlying genetic factors linking both diseases, thus predicting the risk for HCV-related HCC. Aim: The aim of the study was to evaluate and compare the interleukin-28B ( IL-28B ) gene polymorphism in HCV cirrhotic patients with and without HCC. Patients and methods: This case–control study included 40 HCV-infected patients, divided into two equal groups. The first group included 20 cirrhotic patients with HCC and the second group included 20 cirrhotic patients without HCC. IL-28B genotyping was done by using the TaqMan allelic discrimination kit using 7500 Real-Time PCR System (Applied Biosystems). Results: In the present study, the frequencies of CC, CT, and TT genotypes in chronic hepatitis C (CHC) cirrhotic patients with hepatoma were shown to be 15, 30, and 55%, respectively, and 40, 20, and 40 in CHC cirrhotic patients without hepatoma. The prevalence of heterozygous CT and homozygous TT genotypes in CHC cirrhotic patients with hepatoma with allele frequencies among the entire study of the C allele was 30 and 50%, and for the T allele it was 70 and 50%, respectively, in both patients group. A major contribution of the T allele with an increased risk for developing hepatoma cannot be ruled out; CT or TT genotypes and the T allele frequency were 4.00, 3.67, and 2.33 ( P >0.05). Although the difference was statistically nonsignificant due to small sample size, it may be achieved with larger sample size. Conclusion: Our study concluded that IL-28 C/T gene polymorphism may contribute to risk for developing hepatoma in CHC cirrhotic patients.